PCB and preparation method thereof

By setting up a shielding wall made of magnetic composite material in the dielectric layer of the multi-layer printed circuit board, the problem of interference between high-speed signal layers at GHz level is solved, and signal integrity is improved and electromagnetic compatibility is enhanced.

CN119300251AActive Publication Date: 2025-01-10JIAXING MINGRUI ELECTRONIC TECH CO LTD

Patent Information

Application Number
CN202411834365.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-01-10
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to effectively suppress interlayer interference of GHz-level high-speed signals in multi-layer printed circuit boards (PCBs), resulting in an impact on signal integrity.

Method used

A shielding wall made of magnetic composite material is provided in the dielectric layer, grooves are formed by laser etching and magnetic composite material are filled with, combined with magnetron sputtering technology and chemical vapor deposition process to form a magnetic film layer and an oxidation-resistant coating , and finally, a multi-layer PCB board is formed by press synthesis.

Benefits of technology

It significantly improves shielding efficiency, significantly reduces inter-layer crosstalk and electromagnetic interference, and ensures signal integrity and stability, especially in high frequency bands (1MHz-10GHz).

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119300251A_ABST
    Figure CN119300251A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of circuit boards, in particular to a PCB (printed circuit board) and a preparation method thereof, which are characterized in that a groove is formed in a dielectric layer through laser etching, then the groove is filled with a magnetic composite material, and finally, the magnetic composite material is cured on the dielectric layer to form a shielding wall; a copper foil is attached to the surface of the substrate, the surface of the copper foil is coated with photoresist, the signal path pattern is transferred to the photoresist through ultraviolet exposure and development, the copper foil is etched with a ferric chloride solution, and only the portion, on the signal path, of the copper foil is reserved to form a conductive layer; depositing a magnetic thin film layer on the surface of the conductive layer through a magnetron sputtering technology, stacking the magnetic thin film layer, the conductive layer, the dielectric layer, the conductive layer and the substrate layer, then carrying out press-fit molding to form a plurality of layers, forming via holes among the conductive layers on the plurality of layers through a drilling machine, carrying out chemical copper deposition and copper electroplating treatment on the via holes, and finally, carrying out surface treatment. According to the invention, effective suppression of inter-layer signal interference in a GHz-level high-speed signal environment is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of circuit boards, and more particularly to a PCB board and a preparation method thereof. Background Art

[0002] As electronic devices become more complex and perform better, printed circuit boards (PCBs) play an increasingly important role in high-density design and high-speed signal transmission. However, the problem of inter-layer signal interference in multi-layer PCBs has become a key bottleneck restricting their performance improvement.

[0003] As signal frequencies gradually increase to the GHz level, crosstalk and coupling between high-speed signal paths become increasingly important. The transmission of high-speed signals can cause jitter, increased bit error rates, and even eye closure due to electromagnetic interference from adjacent layers, seriously affecting signal integrity.

[0004] CN117677081B proposes a method of embedding resistors in the gold finger area, which optimizes the transmission quality of high-speed signals by improving the impedance continuity of the local area. However, this method is limited to the impedance control of the gold finger area and lacks a comprehensive solution to the high-speed signal interference problem of the multi-layer PCB as a whole.

[0005] Patent CN118175726B proposes a buried groove structure in a PCB, which realizes the function of storing and supplying the target oil inside the PCB by setting an initial buried groove on the dielectric layer and the core board, and using the buried groove to hold the target oil through an intermediate laminated structure formed by pressing. By setting an insulating blind hole in the intermediate laminated structure and connecting it to the buried groove, the quantitative extraction of the oil is realized, the oil supply effect of the signal detection module is optimized, and the interference of the external container on the signal detection is reduced.

[0006] The technology's ability to suppress inter-layer interference in high-speed signal paths is difficult to meet GHz-level signal transmission requirements. Summary of the invention

[0007] To this end, the present invention provides a PCB board and a preparation method thereof, wherein a shielding wall made of a magnetic composite material is arranged in a dielectric layer to effectively suppress inter-layer signal interference in a GHz-level high-speed signal environment.

[0008] To achieve the above object, the present invention provides a PCB board and a method for preparing the same.

[0009] The PCB board has a multi-layer structure and is used to load electronic components. The PCB board includes a substrate layer, a conductive layer, a dielectric layer and a magnetic film layer. The PCB board is prepared by the following method:

[0010] Step S1, forming a groove on the dielectric layer by laser etching, then filling the groove with a magnetic composite material, and finally curing the magnetic composite material on the dielectric layer to form a shielding wall;

[0011] Step S2, laminating copper foil on the surface of the substrate, coating the surface of the copper foil with photoresist, transferring the signal path pattern to the photoresist by ultraviolet light exposure and development, etching the copper foil with ferric chloride solution, and only retaining the copper foil of the signal path portion to form a conductive layer;

[0012] Step S3, depositing a magnetic thin film layer on the surface of the conductive layer by magnetron sputtering technology, and then forming an anti-oxidation coating on the surface of the magnetic thin film layer by chemical vapor deposition process;

[0013] Step S4, stacking the materials in the order of magnetic film layer-conductive layer-dielectric layer-conductive layer-substrate layer and then pressing and forming the layers;

[0014] Step S5: forming via holes between the conductive layers on the multiple layers by a drilling machine, and performing chemical copper deposition and electroplating copper treatment on the via holes.

[0015] Furthermore: in step S1, the cross section of the groove is trapezoidal, the upper width of the groove is 50µm, the lower width is 30µm, and the ratio of the depth to the dielectric layer thickness is 0.8-0.9.

[0016] Furthermore, the magnetic composite material in step S1 comprises, by weight, 40-50 parts of nickel-zinc ferrite particles, 15-25 parts of cobalt-based alloy particles, 25-35 parts of modified epoxy resin, 3-7 parts of liquid crystal polymer, 1-3 parts of nanographene, 2-5 parts of silane coupling agent, 3 parts of boron nitride particles, 2 parts of phosphate flame retardant, and 0.8 parts of fluorine-containing surfactant.

[0017] Further: the specific steps of step S1 are as follows:

[0018] S11, plasma cleaning the surface of the dielectric layer to remove surface dirt, then etching grooves on the surface of the dielectric layer using ultraviolet laser etching equipment, removing materials layer by layer using a multiple scanning method, and plasma spraying the surface of the etched grooves to fill the existing micropores;

[0019] S12, using a micro-spraying machine to spray the glue liquid prepared from the magnetic composite material into the groove, wherein the viscosity of the glue liquid is controlled at 1000-2000cps, the spraying pressure is 0.1-0.2MPa, and the groove is filled by multiple coverings during the spraying process;

[0020] After spraying, the filled dielectric layer is degassed using a vacuum chamber device, with the negative pressure controlled at -0.7MPa for 10 minutes, and the ambient temperature controlled to 40-45°C to accelerate the discharge of bubbles.

[0021] S13, use the micro-sprayer to inject the magnetic composite material glue into the groove again, replenish the groove until it is completely filled, and control the nozzle pressure to 0.1-0.15MPa and the flow rate to 0.05mL / s during the spraying process;

[0022] S14, placing the dielectric layer in a curing device, the curing process is:

[0023] The first temperature control stage: raise the temperature to 55-65°C and maintain it for 8-12 minutes to initially harden the material surface and reduce the fluidity of the material.

[0024] The second temperature control stage: the temperature is raised from 55-65℃ to 85-95℃, and the temperature is slowly raised at a rate of 4-6℃ / min, and maintained for 15-25 minutes to release the internal stress of the material and enhance the stability of the internal structure.

[0025] The third temperature control stage: further increase the temperature to 125-135°C, slowly increase the temperature at a rate of 1-3°C / min, and maintain for 35-45 minutes to complete the cross-linking and curing of the filling material.

[0026] Cooling stage: After curing is completed, the temperature is gradually reduced to room temperature (20-30°C) at a cooling rate of 1-3°C / min to avoid thermal stress caused by rapid cooling.

[0027] Further: the curing process of S14 is:

[0028] The first temperature control stage: the dielectric layer filled with magnetic composite material is placed in a curing device, the temperature is raised to 60°C, and maintained for 10 minutes to initially harden the material surface and reduce the material fluidity;

[0029] The second temperature control stage: the temperature is raised from 60°C to 90°C at a rate of 5°C / min and maintained for 20 minutes to release the internal stress of the material and enhance the stability of the internal structure;

[0030] The third temperature control stage: further raise the temperature to 130°C, slowly increase the temperature at a rate of 2°C / min, and maintain for 40 minutes to complete the cross-linking and curing of the filling material;

[0031] Cooling stage: After curing is completed, the temperature is gradually reduced to room temperature 25°C at a cooling rate of 1°C / min to avoid thermal stress caused by rapid cooling.

[0032] Further: the step S3 specifically includes the following steps:

[0033] S31. During the magnetron sputtering process, a cobalt-iron alloy target material is used, the vacuum degree is controlled at -0.8 to -1.0 MPa, the sputtering power is 200-400 W, high-purity argon gas is introduced, the gas flow rate is 10-20 sccm, and the thickness of the magnetic film layer is 1-3 µm;

[0034] S32, forming an anti-oxidation coating on the surface of the magnetic film layer by chemical vapor deposition process, the coating thickness is 50-100 nm, the reaction pressure is 10-50 Pa, the substrate temperature is 150-250° C., and the reaction time is 10-20 minutes;

[0035] S33. Arrange an oxygen-free copper wire microcoil with a wire diameter of 10-20µm under the magnetic film layer. The coil is embedded to a depth of 20-50µm and fixed by epoxy resin filling. The curing condition is 80-100°C for 30 minutes.

[0036] Further: the preparation process of the magnetic composite material:

[0037] Surface modification of magnetic particles: 45 parts of nickel-zinc ferrite particles and 20 parts of cobalt-based alloy particles are placed in a container.

[0038] Prepare silane coupling agent solution: weigh 3 parts of silane coupling agent according to the formula ratio, dissolve it in anhydrous ethanol, and control its concentration to 3% (mass fraction, w / w).

[0039] Add 3% silane coupling agent ethanol solution into the container, stir evenly, soak for 30 minutes, take out the soaked particles, place them in an oven, and dry them at 80-100°C for 1 hour;

[0040] First stage mixing: add the surface modified particles and 30 parts of modified epoxy resin into a mixing device and stir at 200 rpm for 15 minutes under vacuum;

[0041] Second stage mixing: add 5 parts of liquid crystal polymer, 3 parts of boron nitride particles and 2 parts of phosphate flame retardant to the stirring material, increase the speed to 500-1000rpm, and stir for 20 minutes;

[0042] High-speed shear dispersion: Add 2 parts of nanographene and use a high-speed disperser for dispersion treatment at a shear rate of 2000-3000rpm and a dispersion time of 5 minutes to ensure that the particles are evenly distributed in the matrix;

[0043] Vacuum degassing: Place the mixed materials in a vacuum degassing device and control the vacuum degree at -0.8 to -0.9 MPa. During the degassing process, apply dynamic vibration of 20-50 Hz for 10-15 minutes to remove bubbles in the material.

[0044] Viscosity adjustment: Test the viscosity of the mixed material to ensure that it is controlled within 1000-2000cps, add 0.8 parts of fluorinated surfactant to further improve the fluidity of the material and enhance the filling performance.

[0045] If the material viscosity exceeds the range, add 1%-3% of the total weight of modified epoxy diluent and stir evenly;

[0046] Filtration: Filter the mixed material through a 200-mesh filter to remove any large particles of impurities.

[0047] Furthermore, in S12, after each spraying to form a glue layer with a depth of 1 / 5 of the groove, the filled dielectric layer is degassed at a negative pressure of -0.7 MPa for 10 minutes, and the ambient temperature is controlled at 40-45°C.

[0048] Furthermore: in the step S1, before the grooves are filled on the surface of the dielectric layer, a polyimide masking film with a thickness of 10-20 µm is applied to the outer surface of the dielectric layer, and the groove area is exposed by laser etching, and the masking film is removed after the filling is completed.

[0049] Compared with the shortcomings of the prior art, the beneficial effects of the present invention are:

[0050] The shielding wall made of magnetic composite materials and its curing process can effectively improve the shielding effectiveness in PCB boards and has significant advantages in high frequency bands (1MHz-10GHz). BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 It is a structural schematic diagram of a PCB board of the present invention;

[0052] Figure 2 is a process flow chart of the present invention;

[0053] Figure 3 It is a schematic diagram of the steps of matching the dielectric layer and the shielding film of the present invention;

[0054] Figure 4 This is a curve diagram showing the relationship between porosity and signal loss in the present invention.

[0055] Magnetic film layer 1 , conductive layer 2 , dielectric layer 3 , substrate layer 4 , groove 30 , shielding film 5 . DETAILED DESCRIPTION

[0056] In order to make the objects and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with embodiments; it should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0057] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.

[0058] It should be noted that, in the description of the present invention, terms such as "up", "down", "left", "right", "inside" and "outside" indicating directions or positional relationships are based on the directions or positional relationships shown in the drawings. This is merely for the convenience of description and does not indicate or imply that the device or element must have a specific orientation, be constructed and operated in a specific orientation. Therefore, it cannot be understood as a limitation on the present invention.

[0059] In addition, it should be noted that in the description of the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For those skilled in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0060] The various layers of materials are stacked according to the magnetic film layer-conductive layer-dielectric layer-conductive layer-substrate layer, and then pressed to form a multilayer;

[0061] refer to Figure 1 The PCB board provided in the embodiment of the present invention specifically includes: the PCB board has a multi-layer structure and is used to load electronic components, the PCB board includes a substrate layer, a conductive layer, a dielectric layer and a magnetic film layer, wherein the conductive layer has two layers, and the dielectric layer is arranged between the two conductive layers. The top layer of the PCB board is a magnetic film layer, the bottom layer is a substrate layer, and the two conductive layers are respectively arranged below the magnetic film layer and above the substrate layer.

[0062] refer to Figure 2-Figure 3 The PCB board preparation method provided in the embodiment of the present invention is as follows:

[0063] Step 1: Plasma clean the surface of the dielectric layer 3 to remove surface dirt, and then use ultraviolet laser etching equipment to etch a groove 30 on the surface of the dielectric layer 3. The cross-section of the groove 30 is trapezoidal, the upper width of the groove is 50µm, the lower width is 30µm, and the ratio of depth to dielectric layer thickness is 0.8-0.9.

[0064] The material is removed layer by layer by using a multiple scanning method, and the surface of the etched groove 30 is subjected to plasma spraying to fill the existing micropores.

[0065] In order to inject glue into the groove of the dielectric layer, a polyimide masking film 5 (thickness 10-20 µm) is first coated on the surface of the dielectric layer, and the groove 30 area is precisely cut and exposed by laser etching; the edge of the masking film 5 needs to be aligned with the groove boundary to ensure that the area outside the groove 30 is completely covered.

[0066] Use Nordson EFD's high-precision micro-spraying machine combined with a three-axis motion platform, and set the spraying parameters: pressure: 0.1MPa (initial spraying) to 0.15MPa (supplementary spraying); flow rate: 0.05-0.1 mL / s, to control the amount of glue; distance: the distance between the nozzle and the groove surface is 5-10 mm, and the glue prepared from the magnetic composite material is sprayed into the groove.

[0067] The viscosity of the glue is controlled at 1000-2000cps, and the spraying pressure is 0.1-0.2MPa. During the spraying process, the groove is filled by multiple thin layer coverings. After each spraying, the thickness of the glue is controlled at 1 / 5 of the groove depth. After each layer of spraying, the filled dielectric layer is degassed using a vacuum chamber device. The negative pressure is controlled at -0.7MPa for 10 minutes, and the ambient temperature is controlled to 40-45°C to accelerate the discharge of bubbles.

[0068] Supplementary spraying and removal of masking film: Use the micro-sprayer again to inject the magnetic composite material glue into the groove. During the spraying process, control the nozzle pressure to 0.1-0.15MPa and the flow rate to 0.05mL / s. After the groove is filled completely, remove the masking film and use plasma to clean the surface of the dielectric layer to ensure that there is no glue residue on the outer surface. Before removing the polyimide masking film, the surface of the magnetic composite material glue in the filling groove is tested for flatness to control the flatness error within ±5%. The laser profiler can scan one or more laser lines on the glue surface, and the camera captures the deformation of the light reflection to calculate the surface height distribution. The measured glue surface height data is compared with the ideal plane, and the deviation value of each point is calculated. The measurement results are converted into a color distribution map or a height distribution map using software, so as to quickly locate which areas are higher or lower than the set tolerance.

[0069] After discovering areas that are too high or too low, corresponding correction strategies can be adopted: for areas that are too low, use a micro-sprayer to add a small amount of glue to that area; if the area is too high, use a micro-scraper or special adsorption mechanism to gently remove or smooth the excess glue.

[0070] The dielectric layer is placed in a curing device (the UVLED curing machine) so that the magnetic composite material in the groove 30 is cured to form a shielding wall. The curing process is as follows:

[0071] The first temperature control stage: the dielectric layer filled with magnetic composite material is placed in a curing device, the temperature is raised to 60°C, and maintained for 10 minutes to initially harden the material surface and reduce the material fluidity;

[0072] The second temperature control stage: the temperature is raised from 60°C to 90°C at a rate of 5°C / min and maintained for 20 minutes to release the internal stress of the material and enhance the stability of the internal structure;

[0073] The third temperature control stage: further raise the temperature to 130°C, slowly increase the temperature at a rate of 2°C / min, and maintain for 40 minutes to complete the cross-linking and curing of the filling material;

[0074] Cooling stage: After curing is completed, the temperature is gradually reduced to room temperature 25°C at a cooling rate of 2°C / min to avoid thermal stress caused by rapid cooling.

[0075] The dielectric layer is placed in a curing device (the UVLED curing machine), and the curing process example 2 is as follows:

[0076] The first temperature control stage: raise the temperature to 55°C and maintain it for 8 minutes to initially harden the material surface and reduce the material fluidity.

[0077] The second temperature control stage: the temperature is raised from 55°C to 85°C at a rate of 4°C / min and maintained for 15 minutes to release the internal stress of the material and enhance the stability of the internal structure.

[0078] The third temperature control stage: further raise the temperature to 125°C, slowly increase the temperature at a rate of 1°C / min, and maintain for 35 minutes to complete the cross-linking and curing of the filling material.

[0079] Cooling stage: After curing is completed, the temperature is gradually reduced to room temperature (20°C) at a cooling rate of 1°C / min to avoid thermal stress caused by rapid cooling.

[0080] The dielectric layer is placed in a curing device (the UVLED curing machine), and the curing process example 3 is as follows:

[0081] The first temperature control stage: raise the temperature to 65°C and maintain it for 12 minutes to initially harden the material surface and reduce the material fluidity.

[0082] The second temperature control stage: the temperature is raised from 65°C to 95°C, slowly raised at a heating rate of 6°C / min, and maintained for 25 minutes to release the internal stress of the material and enhance the stability of the internal structure.

[0083] The third temperature control stage: further increase the temperature to 135°C, slowly increase the temperature at a rate of 3°C / min, and maintain for 45 minutes to complete the cross-linking and curing of the filling material.

[0084] Cooling stage: After the curing is completed, the temperature is gradually reduced to room temperature 30°C at a cooling rate of 3°C / minute to avoid thermal stress caused by rapid cooling, and finally achieve the purpose of preparing a shielding wall on the dielectric layer. The function of the shielding wall is to reduce interlayer crosstalk, suppress electromagnetic interference (EMI), and enhance signal integrity.

[0085] Crosstalk refers to the interference of a signal on one signal path to an adjacent signal path, resulting in signal distortion or bit errors.

[0086] The shielding wall forms physical isolation between different signal layers, blocks or weakens the coupling of electromagnetic waves, significantly reduces crosstalk, and ensures the independence and stability of each signal path.

[0087] Among them, electromagnetic interference (EMI) refers to electromagnetic wave interference from external or internal sources, which affects the transmission of sensitive signals on PCB.

[0088] The shielding wall utilizes the electromagnetic shielding properties of high magnetic permeability materials to absorb or reflect unnecessary electromagnetic waves, reduce their impact on internal signals, and improve the electromagnetic compatibility of the PCB.

[0089] Among them, signal integrity refers to the ability of a signal to maintain its original waveform and characteristics during transmission.

[0090] By isolating different signal layers, shielding walls help maintain signal clarity and stability, avoiding signal distortion or distortion caused by interference, thereby ensuring accurate transmission of high-speed signals.

[0091] Step 2: Copper foil with a thickness of 18-35µm is laminated on the surface of the substrate to form the basis of the conductive layer. A photoresist with a thickness of 30µm is coated on the surface of the copper foil. The signal path pattern is transferred to the photoresist through ultraviolet light exposure and development. The exposure energy is 300mJ / cm². The copper foil is etched with a ferric chloride solution at a temperature of 55°C for 90 seconds. Only the copper foil of the signal path is retained to form a conductive layer. The surface of the conductive layer is micro-etched to a roughness of 1-3µm.

[0092] Step 3: Deposit a magnetic thin film layer on the surface of the conductive layer by magnetron sputtering technology. Specifically, a cobalt-iron alloy target is used in the magnetron sputtering process, the vacuum degree is controlled at -0.8 to -1.0 MPa, the sputtering power is 200-400W, high-purity argon gas is introduced, and the gas flow rate is 10-20sccm, so that the thickness of the magnetic thin film layer is 1-3µm.

[0093] An anti-oxidation coating is formed on the surface of the magnetic film layer by a chemical vapor deposition process, the coating thickness is 50-100 nm, the reaction pressure is 10-50 Pa, the substrate temperature is 150-250° C., and the reaction time is 10-20 minutes;

[0094] An oxygen-free copper wire microcoil with a wire diameter of 10-20µm can be laid under the magnetic film layer. The coil embedding depth is 20-50µm and fixed by epoxy resin filling. The curing conditions are 80-100°C and the time is 30 minutes.

[0095] Step 4: stack the materials in the order of magnetic film layer 1 - conductive layer 21 - dielectric layer 3 - conductive layer 22 - substrate layer 4 and press them into a multi-layer structure.

[0096] Step 5: Use a drilling machine to form vias between the conductive layers on the multiple layers, and perform chemical copper deposition and electroplating on the vias.

[0097] The magnetic composite material comprises, by weight, 40-50 parts of nickel-zinc ferrite particles, 15-25 parts of cobalt-based alloy particles, 25-35 parts of modified epoxy resin, 3-7 parts of liquid crystal polymer, 1-3 parts of nanographene, 2-5 parts of silane coupling agent, 3 parts of boron nitride particles, 2 parts of phosphate flame retardant and 0.8 parts of fluorine-containing surfactant.

[0098] The preparation process of the magnetic composite material is as follows:

[0099] Surface modification of magnetic particles: 45 parts of nickel-zinc ferrite particles and 20 parts of cobalt-based alloy particles are placed in a container;

[0100] Prepare silane coupling agent solution: weigh 3 parts of silane coupling agent according to the formula ratio, dissolve it in anhydrous ethanol, and control its concentration to 3% (mass fraction, w / w);

[0101] Add 3% silane coupling agent ethanol solution into the container, stir evenly, soak for 30 minutes, take out the soaked particles, place them in an oven, and dry them at 80-100°C for 1 hour.

[0102] First stage mixing: Add the surface-modified magnetic particles and 30 parts of modified epoxy resin into a mixing device and stir at 200 rpm for 15 minutes under vacuum conditions.

[0103] Second stage mixing: add 5 parts of liquid crystal polymer, 3 parts of boron nitride particles and 2 parts of phosphate flame retardant to the stirring material, increase the speed to 500-1000rpm, and stir for 20 minutes.

[0104] High-speed shear dispersion: Add 2 parts of nanographene and use a high-speed disperser for dispersion. The shear rate is 2000-3000rpm and the dispersion time is 5 minutes to ensure uniform distribution of particles and avoid particle agglomeration.

[0105] Vacuum degassing: Place the mixed material in a vacuum degassing device and control the vacuum degree at -0.8 to -0.9 MPa. During the degassing process, apply 20-50 Hz dynamic vibration for 10-15 minutes to remove bubbles in the material and improve the density and uniformity of the material.

[0106] Viscosity adjustment: Test the viscosity of the mixed material to ensure that it is controlled within 1000-2000cps, add 0.8 parts of fluorinated surfactant to further improve the fluidity of the material and enhance the filling performance.

[0107] If the material viscosity is out of range, add 1%-3% of the total weight of modified epoxy diluent and stir evenly.

[0108] Filtration: Filter the mixed material through a 200-mesh filter to remove any large particles of impurities.

[0109] The preparation process of the magnetic composite material is as follows:

[0110] Surface modification of magnetic particles: 40 parts of nickel-zinc ferrite particles and 15 parts of cobalt-based alloy particles are placed in a container.

[0111] Prepare silane coupling agent solution: weigh 2 parts of silane coupling agent according to the formula ratio, dissolve it in anhydrous ethanol, and control its concentration to 3% (mass fraction, w / w);

[0112] Add 3% silane coupling agent ethanol solution into the container, stir evenly, soak for 30 minutes, take out the soaked particles, place them in an oven, and dry them at 80-100°C for 1 hour.

[0113] First stage mixing: Add the surface-modified magnetic particles and 25 parts of modified epoxy resin into a mixing device and stir at 200 rpm for 15 minutes under vacuum.

[0114] Second stage mixing: add 3 parts of liquid crystal polymer, 3 parts of boron nitride particles and 2 parts of phosphate flame retardant to the stirring material, increase the speed to 500-1000rpm, and stir for 20 minutes.

[0115] High-speed shear dispersion: Add 2 parts of nanographene and use a high-speed disperser for dispersion treatment with a shear rate of 2000-3000rpm and a dispersion time of 5 minutes to ensure that the particles are evenly distributed in the matrix.

[0116] Vacuum degassing: Place the mixed material in a vacuum degassing device and control the vacuum degree at -0.8 to -0.9 MPa. During the degassing process, apply 20-50 Hz dynamic vibration for 10-15 minutes to remove bubbles in the material.

[0117] Viscosity adjustment: Test the viscosity of the mixed material to ensure that it is controlled within 1000-2000cps, add 0.8 parts of fluorinated surfactant to further improve the fluidity of the material and enhance the filling performance.

[0118] If the material viscosity is out of range, add 1%-3% of the total weight of modified epoxy diluent and stir evenly.

[0119] Filtration: Filter the mixed material through a 200-mesh filter to remove any large particles of impurities.

[0120] The preparation process of the magnetic composite material is as follows:

[0121] Surface modification of magnetic particles: 50 parts of nickel-zinc ferrite particles and 25 parts of cobalt-based alloy particles were placed in a container;

[0122] Prepare silane coupling agent solution: weigh 2 parts of silane coupling agent according to the formula ratio, dissolve it in anhydrous ethanol, and control its concentration to 3% (mass fraction, w / w);

[0123] Add 3% silane coupling agent ethanol solution into the container, stir evenly, soak for 30 minutes, take out the soaked particles, place them in an oven, and dry them at 80-100°C for 1 hour.

[0124] First stage mixing: Add the surface-modified magnetic particles and 35 parts of modified epoxy resin into a mixing device and stir at a speed of 200 rpm for 15 minutes under vacuum conditions.

[0125] Second stage mixing: add 7 parts of liquid crystal polymer, 3 parts of boron nitride particles and 2 parts of phosphate flame retardant to the stirring material, increase the speed to 500-1000rpm, and stir for 20 minutes.

[0126] High-speed shear dispersion: Add 2 parts of nanographene and use a high-speed disperser for dispersion treatment with a shear rate of 2000-3000rpm and a dispersion time of 5 minutes to ensure that the particles are evenly distributed in the matrix.

[0127] Vacuum degassing: Place the mixed material in a vacuum degassing device and control the vacuum degree at -0.8 to -0.9 MPa. During the degassing process, apply 20-50 Hz dynamic vibration for 10-15 minutes to remove bubbles in the material.

[0128] Viscosity adjustment: Test the viscosity of the mixed material to ensure that it is controlled within 1000-2000cps, add 0.8 parts of fluorinated surfactant to further improve the fluidity of the material and enhance the filling performance.

[0129] If the material viscosity is out of range, add 1%-3% of the total weight of modified epoxy diluent and stir evenly.

[0130] Filtration: Filter the mixed material through a 200-mesh filter to remove any large particles of impurities.

[0131] Embodiment 1:

[0132] The magnetic composite material glue obtained in Example 1 of the preparation process of the magnetic composite material is sprayed on the dielectric layer through a high-precision micro-sprayer of Nordson EFD. The specific process is as described above. After the groove is filled completely, the masking film is removed, and the surface of the dielectric layer is cleaned with plasma to ensure that there is no glue residue on the outer surface. Finally, the dielectric layer is placed in a curing device (the UVLED curing machine) and the method of Example 1 of the curing process is adopted to obtain a dielectric layer with a shielding wall, and then the dielectric layer is combined with the conductive layer and the magnetic film layer obtained in step 2 and step 3. According to the method of step 4: the magnetic film layer-conductive layer-dielectric layer-conductive layer-substrate layer is stacked and then pressed into a multilayer, and finally a multilayer PCB board is obtained after step 5, which is named sample 1.

[0133] Embodiment 2:

[0134] The magnetic composite material glue obtained in Example 1 of the preparation process of the magnetic composite material is sprayed on the dielectric layer through a high-precision micro-sprayer of Nordson EFD. The specific process is as described above. After the groove is filled completely, the masking film is removed, and the surface of the dielectric layer is cleaned with plasma to ensure that there is no glue residue on the outer surface. Finally, the dielectric layer is placed in a curing device (the UVLED curing machine) and the method of Example 2 of the curing process is adopted to obtain a dielectric layer with a shielding wall, and then the dielectric layer is combined with the conductive layer and the magnetic film layer obtained in Steps 2 and 3. According to Step 4, the magnetic film layer-conductive layer-dielectric layer-conductive layer-substrate layer are stacked and pressed into a multilayer, and finally a multilayer PCB board is obtained after Step 5, which is named Sample 2.

[0135] Embodiment three:

[0136] The magnetic composite material glue obtained in Example 1 of the preparation process of the magnetic composite material is sprayed on the dielectric layer through a high-precision micro-sprayer of Nordson EFD. The specific process is as described above. After the groove is filled until it is completely filled, the masking film is removed, and the surface of the dielectric layer is cleaned with plasma to ensure that there is no glue residue on the outer surface. Finally, the dielectric layer is placed in a curing device (the UVLED curing machine) and the implementation method of Example 3 of the curing process is adopted to obtain a dielectric layer with a shielding wall, and then the dielectric layer is combined with the conductive layer and the magnetic film layer obtained in Steps 2 and 3. According to the method of Step 4: the magnetic film layer-conductive layer-dielectric layer-conductive layer-substrate layer is stacked and then pressed into a multilayer, and finally a multilayer PCB board is obtained after Step 5, which is named Sample 3.

[0137] Embodiment 4:

[0138] The magnetic composite material glue obtained in Example 2 of the preparation process of the magnetic composite material is sprayed on the dielectric layer through a high-precision micro-sprayer of Nordson EFD. The specific process is as described above. After the groove is filled completely, the masking film is removed, and the surface of the dielectric layer is cleaned with plasma to ensure that there is no glue residue on the outer surface. Finally, the dielectric layer is placed in a curing device (the UVLED curing machine) and the method of Example 1 of the curing process is adopted to obtain a dielectric layer with a shielding wall, and then the dielectric layer is combined with the conductive layer and the magnetic film layer obtained in Steps 2 and 3. According to Step 4: the magnetic film layer-conductive layer-dielectric layer-conductive layer-substrate layer is stacked and then pressed into a multilayer, and finally a multilayer PCB board is obtained after Step 5, which is named Sample 4.

[0139] Embodiment five:

[0140] The magnetic composite material glue obtained in Example 2 of the preparation process of the magnetic composite material is sprayed on the dielectric layer through a high-precision micro-sprayer of Nordson EFD. The specific process is as described above. After the groove is filled until it is completely filled, the masking film is removed, and the surface of the dielectric layer is cleaned with plasma to ensure that there is no glue residue on the outer surface. Finally, the dielectric layer is placed in a curing device (the UVLED curing machine) and the implementation method of Example 2 of the curing process is adopted to obtain a dielectric layer with a shielding wall, and then the dielectric layer is combined with the conductive layer and the magnetic film layer obtained in Steps 2 and 3. According to the method of Step 4: the magnetic film layer-conductive layer-dielectric layer-conductive layer-substrate layer is stacked and then pressed into a multilayer, and finally a multilayer PCB board is obtained after Step 5, which is named Sample 5.

[0141] Embodiment six:

[0142] The magnetic composite material glue obtained in Example 2 of the preparation process of the magnetic composite material is sprayed on the dielectric layer through a high-precision micro-sprayer of Nordson EFD. The specific process is as described above. After the groove is filled until it is completely filled, the masking film is removed, and the surface of the dielectric layer is cleaned with plasma to ensure that there is no glue residue on the outer surface. Finally, the dielectric layer is placed in a curing device (the UVLED curing machine) and the implementation method of Example 3 of the curing process is adopted to obtain a dielectric layer with a shielding wall, and then the dielectric layer is combined with the conductive layer and the magnetic film layer obtained in Steps 2 and 3. According to the method of Step 4: the magnetic film layer-conductive layer-dielectric layer-conductive layer-substrate layer is stacked and then pressed into a multilayer, and finally a multilayer PCB board is obtained after Step 5, which is named Sample 6.

[0143] Embodiment seven:

[0144] The magnetic composite material glue obtained in Example 3 of the preparation process of the magnetic composite material is sprayed on the dielectric layer through a high-precision micro-sprayer of Nordson EFD. The specific process is as described above. After the groove is filled completely, the masking film is removed, and the surface of the dielectric layer is cleaned with plasma to ensure that there is no glue residue on the outer surface. Finally, the dielectric layer is placed in a curing device (the UVLED curing machine) and the implementation method of Example 1 of the curing process is adopted to obtain a dielectric layer with a shielding wall, and then the dielectric layer is combined with the conductive layer and the magnetic film layer obtained in Steps 2 and 3. According to Step 4: the magnetic film layer-conductive layer-dielectric layer-conductive layer-substrate layer is stacked and then pressed into a multilayer, and finally a multilayer PCB board is obtained after Step 5, which is named Sample 7.

[0145] Embodiment eight:

[0146] The magnetic composite material glue obtained in Example 3 of the preparation process of the magnetic composite material is sprayed on the dielectric layer through a high-precision micro-sprayer of Nordson EFD. The specific process is as described above. After the groove is filled completely, the masking film is removed, and the surface of the dielectric layer is cleaned with plasma to ensure that there is no glue residue on the outer surface. Finally, the dielectric layer is placed in a curing device (the UVLED curing machine) and the implementation method of Example 2 of the curing process is adopted to obtain a dielectric layer with a shielding wall, and then the dielectric layer is combined with the conductive layer and the magnetic film layer obtained in Steps 2 and 3. According to the method of Step 4: the magnetic film layer-conductive layer-dielectric layer-conductive layer-substrate layer is stacked and then pressed into a multilayer, and finally a multilayer PCB board is obtained after Step 5, which is named Sample 8.

[0147] Embodiment nine:

[0148] The magnetic composite material glue obtained in Example 3 of the preparation process of the magnetic composite material is sprayed on the dielectric layer through a high-precision micro-sprayer of Nordson EFD. The specific process is as described above. After the groove is filled completely, the masking film is removed, and the surface of the dielectric layer is cleaned with plasma to ensure that there is no glue residue on the outer surface. Finally, the dielectric layer is placed in a curing device (the UVLED curing machine) and the implementation method of Example 3 of the curing process is adopted to obtain a dielectric layer with a shielding wall, and then the dielectric layer is combined with the conductive layer and the magnetic film layer obtained in Steps 2 and 3. According to the method of Step 4: the magnetic film layer-conductive layer-dielectric layer-conductive layer-substrate layer is stacked and pressed into a multilayer, and finally a multilayer PCB board is obtained after Step 5, which is named Sample 9.

[0149] Shielding effectiveness test: Test the shielding effectiveness of the sample in the frequency band from 1 MHz to 10 GHz, in dB, to verify the performance of the sample in signal shielding.

[0150] Thermal conductivity test: Use a laser thermal conductivity meter to measure the thermal conductivity of the sample (unit: W / m·K), and perform a thermal cycle stability test at the same time.

[0151] Chemical stability test: The samples were placed in acidic (pH=3) and alkaline (pH=10) environments to analyze the retention of shielding effectiveness and mechanical properties.

[0152] Signal integrity testing: Measures signal loss and crosstalk in high-speed signal transmission scenarios to verify the suitability of samples in electronic devices.

[0153] Comparative data table 1 obtained by testing sample 1, sample 2, sample 3, sample 4, sample 5, sample 6, sample 7, sample 8 and sample 9:

[0154]

[0155] Comparative Example 1: The magnetic composite material glue obtained in Example 1 of the preparation process of the magnetic composite material is sprayed on the dielectric layer through a high-precision micro-sprayer of Nordson EFD. This specific step adopts the specific spraying method in Sample 1 to spray it into the groove of the dielectric layer, and then the dielectric layer is sent to a curing device (the UVLED curing machine) for curing. When it is fixed, the constant temperature curing temperature is set to 120°C and maintained for 60 minutes to complete the cross-linking curing. After the curing is completed, the sample is cooled to room temperature (20-30°C) by natural cooling, and finally a dielectric layer is obtained. The dielectric layer is combined with the conductive layer and the magnetic film layer obtained in Steps 2 and 3, and the magnetic film layer is stacked according to Step 4: the magnetic film layer-conductive layer-dielectric layer-conductive layer-substrate layer is stacked and pressed into a multilayer, and finally a multilayer PCB board is obtained after Step 5, which is named Sample 10.

[0156] Comparative Example 2: The magnetic composite material glue obtained in Example 1 of the preparation process of the magnetic composite material is sprayed on the dielectric layer through a high-precision micro-sprayer of Nordson EFD. This specific step adopts the specific spraying method in Sample 1 to spray it into the groove of the dielectric layer, and then the dielectric layer is sent to a curing device (the UVLED curing machine) for curing, and the initial temperature is set to 40°C, and the temperature is continuously increased to 130°C at a rate of 3°C / minute. After reaching the target temperature, the constant temperature is maintained for 40 minutes to complete cross-linking and curing. After the curing is completed, the temperature is lowered to room temperature (20-30°C) at a rate of 1°C / minute to finally obtain a dielectric layer. The dielectric layer is combined with the conductive layer and the magnetic film layer obtained in Steps 2 and 3, and the magnetic film layer is stacked according to Step 4: the magnetic film layer-conductive layer-dielectric layer-conductive layer-substrate layer is stacked and pressed into a multilayer, and finally a multilayer PCB board is obtained after Step 5, which is named Sample 11.

[0157] Table 2 is based on the data comparison of sample 10, sample 11 and sample 1:

[0158]

[0159] According to Table 1, Table 2 and Figure 4 Mesoporosity versus signal loss.

[0160] The following analysis is conducted from the perspective of the different samples (Sample 1 to Sample 9) finally obtained, focusing on their performance in key indicators such as shielding effectiveness, thermal conductivity, porosity, thermal stability, chemical stability and signal loss, and exploring the relationship between these performance indicators and the material formulations and process conditions used in each.

[0161] Sample 1 (Formulation Example 1 + Curing Process Example 1):

[0162] Shielding effectiveness is 20dB, thermal conductivity is 8W / m·K, porosity is <0.3%, thermal stability is 95%, chemical stability (acid / alkali retention rate) is 92 / 94, and signal loss is 0.15dB.

[0163] Overall, sample 1 performs well in all indicators: high shielding effectiveness, outstanding thermal conductivity, extremely low porosity, good thermal and chemical stability, and relatively low signal loss. This sample can be used as a benchmark for optimizing processes and formulations.

[0164] Sample 2 (Formulation Example 1 + Curing Process Example 2):

[0165] Shielding effectiveness 17dB, thermal conductivity 7W / m·K, porosity 0.6%, thermal stability 88%, chemical stability 87 / 89, signal loss 0.20dB.

[0166] Compared with sample 1, the shielding effectiveness and thermal conductivity of sample 2 are slightly reduced, the porosity is increased, and the thermal and chemical stability are also slightly poor, resulting in increased signal loss. This result shows that changing the curing process parameters will affect the density and internal structure of the material, thereby affecting the overall performance.

[0167] Sample 3 (Formula Example 1 + Curing Process Example 3):

[0168] Shielding effectiveness 18dB, thermal conductivity 7.5W / m·K, porosity 0.4%, thermal stability 91%, chemical stability 89 / 90, signal loss 0.18dB.

[0169] Although sample 3 is slightly lower than sample 1, the overall performance is still at a high level, indicating that the change in curing conditions has a significant impact on the internal stress release and porosity control of the material. The performance of this sample in various indicators is relatively balanced.

[0170] Sample 4 (Formula Example 2 + Curing Process Example 1):

[0171] Shielding effectiveness 16dB, thermal conductivity 6.8W / m·K, porosity 0.7%, thermal stability 85%, chemical stability 84 / 86, signal loss 0.25dB.

[0172] Compared with the sample using formula example 1, the indicators of sample 4 are generally lower than those of sample 1, indicating that changes in the formula (such as reducing the proportion of magnetic particles or adjusting the content of liquid crystal polymer) will affect the density and performance of the material. Under the same curing process, formula adjustment is an important factor leading to performance changes.

[0173] Sample 5 (Formula Example 2 + Curing Process Example 2):

[0174] Shielding effectiveness 15dB, thermal conductivity 6.6W / m·K, porosity 0.8%, thermal stability 83%, chemical stability 82 / 84, signal loss 0.27dB.

[0175] Compared with sample 4, it further decreases. It can be seen that based on the "weaker" formula, if the curing process control is not as fine as in examples 1 and 3, it will lead to increased porosity, reduced thermal and chemical stability, and ultimately a significant increase in signal loss.

[0176] Sample 6 (Formula Example 2 + Curing Process Example 3):

[0177] Shielding effectiveness 17dB, thermal conductivity 7.2W / m·K, porosity 0.5%, thermal stability 89%, chemical stability 86 / 88, signal loss 0.19dB.

[0178] In comparison with samples 2 and 5, the improvement of the curing process of sample 6 (Example 3) can obviously make up for the shortcomings of the formula, so that the performance has significantly improved compared with samples 4 and 5. This shows that precise curing conditions can help reduce porosity and improve the overall performance of the material.

[0179] Sample 7 (Formula Example 3 + Curing Process Example 1):

[0180] Shielding effectiveness 19dB, thermal conductivity 7.8W / m·K, porosity <0.4%, thermal stability 93%, chemical stability 90 / 92, signal loss 0.16dB.

[0181] Compared with Sample 1, Sample 7 also exhibits excellent overall performance, which indicates that Formula Example 3, with a high magnetic particle content and a suitable additive ratio, can achieve high performance close to or even slightly inferior to that of Sample 1 after a suitable curing process (Example 1), and has good development potential.

[0182] Sample 8 (Formula Example 3 + Curing Process Example 2):

[0183] Shielding effectiveness 18dB, thermal conductivity 7.4W / m·K, porosity 0.5%, thermal stability 92%, chemical stability 89 / 91, signal loss 0.17dB.

[0184] Compared with sample 7, it is slightly worse, but still at a good level. This shows that under the high-performance formula (Example 3), even if the curing conditions are relatively less stringent than those in Example 1, it can still maintain good performance.

[0185] Sample 9 (Formula Example 3 + Curing Process Example 3):

[0186] Shielding effectiveness 19.5dB, thermal conductivity 7.9W / m·K, porosity <0.4%, thermal stability 94%, chemical stability 91 / 93, signal loss 0.16dB.

[0187] Sample 9 performs similarly to or even better than samples 1 and 7, with a shielding effectiveness of nearly 20 dB, a porosity of less than 0.4%, and a signal loss of only 0.16 dB. This shows that when a high-performance formula (Example 3) meets a sophisticated curing process (Example 3), the best overall performance can be achieved. This sample is representative, indicating that the best match between material formula and process conditions can achieve the best performance.

[0188] Different formulations (Example 1, Example 2, Example 3) and different curing processes (Example 1, Example 2, Example 3) jointly determine the comprehensive performance of the final samples. High magnetic particle ratio, high-quality surface modification and appropriate additive ratio can bring better shielding and thermal conductivity and lower porosity.

[0189] In each sample, the lower the porosity (<0.4%), the lower the signal loss, and the higher the shielding effectiveness and stability. This shows that by optimizing the spraying process, vacuum degassing and curing conditions, bubbles and internal defects can be effectively reduced, achieving better dielectric uniformity and electromagnetic shielding performance.

[0190] Under the same formula, different curing heating, constant temperature, and cooling stage strategies directly affect the internal stress release and curing uniformity. Gradual heating and cooling and sufficient constant temperature time can improve thermal, chemical stability and electrical performance, reduce internal stress, and thus optimize signal integrity and shielding effect.

[0191] Samples 1, 7, and 9, which have excellent performance, provide feasible references for practical applications. In actual production, appropriate formulas and curing solutions can be selected according to the equipment's operating frequency band, thermal management requirements, and environmental tolerance requirements to achieve optimal performance.

[0192] By analyzing the samples, the interactive relationship between material formula, process parameters and final performance was clarified. By optimizing the component ratio and microstructure control of the magnetic composite material, combined with refined curing process and spraying conditions, multi-layer PCB products with high shielding effectiveness, low signal loss, high reliability and excellent environmental adaptability can be prepared.

[0193] The main difference between Comparative Example 1 (Sample 10) and Comparative Example 2 (Sample 11) lies in the control method of the curing conditions: the former adopts a relatively simplified constant temperature curing and natural cooling, while the latter adopts gradual heating and cooling control.

[0194] Comparison with Sample 1, Sample 7 and Sample 9:

[0195] Samples 1, 7, and 9 represent highly optimized formulations and curing processes, which use a multi-stage heating and insulation strategy to achieve surface curing, internal stress release, and deep crosslinking in different temperature ranges. This meticulous temperature control process helps to significantly reduce porosity and internal stress, thereby improving shielding effectiveness, thermal conductivity, and signal integrity.

[0196] In contrast, sample 10 (single constant temperature curing) lacks the staged pre-hardening and stress release process, resulting in more residual internal stress and less-than-expected porosity control, which results in inferior performance to the optimized sample. Although sample 11 has a certain degree of temperature rise and fall control, it is still only a single progressive curve, rather than multi-stage fine-tuning, and is still inferior to the optimal solution in terms of stress release and porosity control.

[0197] Comparison with Sample 2 and Sample 5:

[0198] Samples 2 and 5 also use relatively simple curing conditions, and their performance generally lags behind the most optimized samples (such as samples 1, 7, and 9). Samples 10 and 11, as comparative solutions (i.e., comparative references), have similar problems in process refinement as samples 2 and 5: the curing speed and stress release in each temperature range cannot be accurately controlled, resulting in relatively average overall performance. This situation is not the best choice for high-speed PCBs with high requirements for shielding effectiveness, thermal conductivity, and low signal loss.

[0199] Correlation between porosity and signal loss:

[0200] From the previous analysis, we know that porosity is one of the key influencing factors. The curing method using a single constant temperature (sample 10) or only a linear heating and cooling curve (sample 11) is difficult to effectively force out the tiny bubbles in the material like multi-stage fine curing, resulting in a higher porosity. This will directly lead to increased non-uniformity of the dielectric layer, causing increased signal transmission loss and reduced shielding effectiveness.

[0201] Stress relief and structural uniformity:

[0202] The curing conditions of Samples 10 and 11 are not as fine as the aforementioned best samples (such as Samples 1 and 9) in terms of the precision of stress relief. The strategy of multi-stage control (such as low temperature pre-hardening, then medium temperature slow rise for stress release, and finally high temperature complete curing and slow cooling) is crucial to improving the uniformity and stability of the material structure. These refinement measures are not reflected in the comparative examples, so their performance is not as good as the optimized embodiments in terms of porosity, thermal stability, shielding effectiveness and signal loss.

[0203] The above descriptions are merely embodiments of the present invention and are not intended to limit the present invention. Any common changes and substitutions made by those skilled in the art within the technical solution of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a PCB board, characterized in that: The following steps are involved: Step S1, forming a groove on the dielectric layer by laser etching, then filling the groove with a magnetic composite material, and finally curing the magnetic composite material on the dielectric layer to form a shielding wall; Step S2, laminating copper foil on the surface of the substrate, coating the surface of the copper foil with photoresist, transferring the signal path pattern to the photoresist by ultraviolet light exposure and development, etching the copper foil with ferric chloride solution, and only retaining the copper foil of the signal path portion to form a conductive layer; Step S3, depositing a magnetic thin film layer on the surface of the conductive layer by magnetron sputtering technology, and then forming an anti-oxidation coating on the surface of the magnetic thin film layer by chemical vapor deposition process; Step S4, stacking the materials in the order of magnetic film layer-conductive layer-dielectric layer-conductive layer-substrate layer and then pressing and forming the layers; Step S5: forming via holes between the conductive layers on the multiple layers by a drilling machine, and performing chemical copper deposition and electroplating copper treatment on the via holes.

2. A method for preparing a PCB board according to claim 1, characterized in that: In the step S1, the cross section of the groove is trapezoidal, the upper width of the groove is 50 μm, the lower width is 30 μm, and the ratio of the depth to the dielectric layer thickness is 0.8-0.

9.

3. A method for preparing a PCB board according to claim 2, characterized in that: The magnetic composite material in step S1 comprises, by weight, 40-50 parts of nickel-zinc ferrite particles; 15-25 parts of cobalt-based alloy particles; 25-35 parts of modified epoxy resin; 3-7 parts of liquid crystal polymer; 1-3 parts of nanographene; 2-5 parts of silane coupling agent, 3 parts of boron nitride particles; 2 parts of phosphate flame retardant; and 0.8 parts of fluorine-containing surfactant.

4. A method for preparing a PCB board according to claim 3, characterized in that: The specific steps of step S1 are as follows: S11, plasma cleaning the surface of the dielectric layer to remove surface dirt, then etching grooves on the surface of the dielectric layer using ultraviolet laser etching equipment, removing materials layer by layer using a multiple scanning method, and plasma spraying the surface of the etched grooves to fill the existing micropores; S12, using a micro-spraying machine to spray the glue liquid prepared from the magnetic composite material into the groove, wherein the viscosity of the glue liquid is controlled at 1000-2000cps, the spraying pressure is 0.1-0.2MPa, and the groove is filled by multiple thin layer covering during the spraying process; After spraying, the filled dielectric layer is degassed using a vacuum chamber device, with the negative pressure controlled at -0.7MPa for 10 minutes, and the ambient temperature controlled to 40-45°C to accelerate the discharge of bubbles. S13, use the micro-sprayer to inject the magnetic composite material glue into the groove again, replenish the groove until it is completely filled, and control the nozzle pressure to 0.1-0.15MPa and the flow rate to 0.05mL / s during the spraying process; S14, placing the dielectric layer in a curing device for curing, the curing process is: The first temperature control stage: raise the temperature to 55-65°C and maintain it for 8-12 minutes to initially harden the material surface and reduce the material fluidity. The second temperature control stage: the temperature is raised from 55-65℃ to 85-95℃, and the temperature is slowly raised at a rate of 4-6℃ / min, and maintained for 15-25 minutes to release the internal stress of the material and enhance the stability of the internal structure. The third temperature control stage: further increase the temperature to 125-135°C, slowly increase the temperature at a rate of 1-3°C / min, and maintain for 35-45 minutes to complete the cross-linking and curing of the filling material. Cooling stage: After curing is completed, the temperature is gradually reduced to room temperature (20-30°C) at a cooling rate of 1-3°C / min to avoid thermal stress caused by rapid cooling.

5. A method for preparing a PCB board according to claim 4, characterized in that: The curing process of S14 is as follows: The first temperature control stage: the dielectric layer filled with magnetic composite material is placed in a curing device, the temperature is raised to 60°C, and maintained for 10 minutes to initially harden the material surface and reduce the material fluidity; The second temperature control stage: the temperature is raised from 60°C to 90°C, slowly raised at a heating rate of 5°C / min, and maintained for 20 minutes to release the internal stress of the material; The third temperature control stage: further raise the temperature to 130°C, slowly increase the temperature at a rate of 2°C / min, and maintain for 40 minutes to complete the cross-linking and curing of the filling material; Cooling stage: After curing is completed, the temperature is gradually reduced to room temperature 25°C at a cooling rate of 1°C / min to avoid thermal stress caused by rapid cooling.

6. A method for preparing a PCB board according to claim 1, characterized in that: The step S3 specifically comprises the following steps: S31. During the magnetron sputtering process, a cobalt-iron alloy target material is used, the vacuum degree is controlled at -0.8 to -1.0 MPa, the sputtering power is 200-400 W, high-purity argon gas is introduced, the gas flow rate is 10-20 sccm, and the thickness of the magnetic film layer is 1-3 µm; S32, forming an anti-oxidation coating on the surface of the magnetic film layer by chemical vapor deposition process, the coating thickness is 50-100nm, the reaction pressure is 10-50Pa, the substrate temperature is 150-250°C, and the reaction time is 10-20 minutes; S33. Arrange an oxygen-free copper wire microcoil with a wire diameter of 10-20µm under the magnetic film layer. The coil is embedded to a depth of 20-50µm and fixed by epoxy resin filling. The curing condition is 80-100°C for 30 minutes.

7. A method for preparing a PCB board according to claim 3, characterized in that: The preparation process of the magnetic composite material: Surface modification of magnetic particles: 45 parts of nickel-zinc ferrite particles and 20 parts of cobalt-based alloy particles are placed in a container; Prepare a silane coupling agent solution: weigh 3 parts of silane coupling agent according to the formula ratio, dissolve it in anhydrous ethanol, and control its concentration to 3% (mass fraction, w / w); Add 3% silane coupling agent ethanol solution into the container and stir evenly. The treatment time is 30 minutes. Take out the treated particles, place them in an oven, and dry them at 80-100°C for 1 hour. First stage mixing: add the surface modified particles and 30 parts of modified epoxy resin into a mixing device and stir at 200 rpm for 15 minutes under vacuum; Second stage mixing: add 5 parts of liquid crystal polymer, 3 parts of boron nitride particles and 2 parts of phosphate flame retardant to the stirring material, increase the speed to 500-1000rpm, and stir for 20 minutes; High-speed shear dispersion: Add 2 parts of nanographene and use a high-speed disperser for dispersion treatment at a shear rate of 2000-3000rpm and a dispersion time of 5 minutes to ensure that the particles are evenly distributed in the matrix; Vacuum degassing: Place the mixed materials in a vacuum degassing device and control the vacuum degree at -0.8 to -0.9 MPa. During the degassing process, apply dynamic vibration of 20-50 Hz for 10-15 minutes to remove bubbles in the material. Viscosity adjustment: Test the viscosity of the mixed material to ensure that it is controlled within 1000-2000cps, add 0.8 parts of fluorinated surfactant to further improve the fluidity of the material and enhance the filling performance. If the material viscosity exceeds the range, add 1%-3% of the total weight of modified epoxy diluent and stir evenly; Filtration: Filter the mixed material through a 200-mesh filter to remove any large particles of impurities.

8. A method for preparing a PCB board according to claim 4, characterized in that: Specifically, in S12, after each spraying to form a glue layer with a depth of 1 / 5 of the groove, the filled dielectric layer is degassed at a negative pressure of -0.7 MPa for 10 minutes, and the ambient temperature is controlled at 40-45°C.

9. A method for preparing a PCB board according to claim 8, characterized in that: In the step S1, before the grooves are filled on the surface of the dielectric layer, a polyimide masking film with a thickness of 10-20 µm is applied to the outer surface of the dielectric layer, and the groove area is exposed by laser etching. The masking film is removed after the filling is completed.

10. A PCB board, characterized in that: The PCB is manufactured by the method for preparing the PCB according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • PCB circuit board, signal detection device and PCB circuit board preparation method

    CN118175726B

  • Circuit board with embedded magnetic material and for wireless charging and manufacturing method

    CN104602451A

  • High-permeability magnetic film and preparation method thereof

    CN106601429A

  • Electromagnetic shielding material with a three-layer structure and preparation method thereof

    CN111590987A

  • Circuit board processing method and circuit board

    CN114630504A

Cited By

  • Manufacturing method of cavity module with low signal loss and PCB

    CN121013251A